Effect of pegaptanib sodium 0.3 mg intravitreal injections (Macugen) in intraocular pressure: posthoc analysis from V.I.S.I.O.N. study - Boyer, David S; Goldbaum, Mauro; Leys, Anita M; Starita, Carla (British journal of ophthalmology, 2014)
Objective To assess the rate of pegaptanib-associated sustained intraocular pressure (IOP) elevation. Methods A posthoc analysis was conducted on all IOP measurements, except the immediate 30-min postinjection, from all subjects randomised to pegaptanib 0.3 mg or sham injections continuously in the first 2 years of the Vascular endothelial growth factor Inhibition Study in Ocular Neovascularisation (V.I.S.I.O.N.) study. Measurements were taken with Goldmann applanation tonometer or Tonopen, except at baseline and in cases of an IOP reading >30 mm Hg when a Goldmann applanation tonometer was mandatory. Results Of 221 subjects, IOP measurements ≥22 mm Hg were seen in 28/114 and 23/107 subjects of the pegaptanib and sham subgroups, respectively (p=0.6338) and measurements ≥24 mm Hg were observed in eight and eight subjects in the pegaptanib and sham groups, respectively. More than two measurements ≥22 mm Hg occurred in six and 10 subjects (p=0.3025), and more than two measurements ≥24 mm Hg were observed in one and four subjects in the pegaptanib and sham groups, respectively. One patient with sustained IOP elevation in the pegaptanib study group, and four in the sham group, had IOP lowering medication added during the course of the study. No subject required glaucoma surgery. Conclusions In V.I.S.I.O.N., after 2 years, there was no evidence of sustained IOP elevation associated with pegaptanib 0.3 mg use. Trial registration number NCT00321997.